Analysis and prediction of relative survival trends in patients with non-Hodgkin lymphoma in the United States using a model-based period analysis method - Xie, Shuping; Yu, Zhong; Feng, Aozi; Zheng, Shuai; Li, Yunmei; Zeng, You; Lyu, Jun (Frontiers in Oncology, 2022)
Background: To assess the long-term prognosis of non-Hodgkin lymphoma (NHL) with the aim of providing a scientific basis for developing active prevention and therapy techniques for NHL. Methods: A period analysis was used to evaluate the improvement in long-term prognosis of patients with NHL from 2001 to 2015, and a generalized linear model was developed to predict the 5-year relative survival rates of patients during 2016–2020 based on data from the SEER database stratified by age, sex, race, histology, clinical stage, socioeconomic status, and disease site. Results: In this study, relative survival improved for all NHL, although the extent of improvement varied by sex, age group and lymphoma subtype. Survival improvement was also noted for NHL subtypes, although the extent varied, with marginal-zone lymphoma having the highest 5-year relative survival rate (91.7%) followed by follicular lymphoma (89.7%) and chronic lymphocytic leukemia/small lymphocytic lymphoma (81.5%). An improving survival rate over time in both sexes, although females seemed to have a slightly higher survival rate than males for all subtypes. For NHL, 5-year survival increases over time for all age groups expect for peripheral T-Cell Lymphoma. Survival rates in older age groups has been consistently lower compared to younger age groups throughout the study period. Furthermore, the study demonstrated that the survival rates for all NHL were lower in patients of lower socioeconomic status, black race and IV stage. Conclusion: Overall, patient survival rates for NHL gradually improved during 2001–2015, and this trend was predicted to continue during 2016–2020. This progress is likely to be due to the efficacy of new treatment options, as well as improvements around environmental risk factors, diagnostic procedures, and other factors. Analysis by NHL subtype and subgroups revealed that only for certain subtypes were some subgroups at greater risk than others, indicating that etiology and risk factors may differ by subtype. Identification of population-specific prevention strategies and treatments for each subtype can be aided by understanding these variations.